À margem em The bluest eye, de Toni Morrison: negritude, identidade e crítica social - Lopes, Mirna Leisi Coelho (2009)
The contemporary North American fiction (African American) presents concerns regarding the identity of African-Americans. There is a need, through the literary text, to establish a dialogue with the myths and historical models for the legacy tradition of slaves from Africa. The aim of this study is to analyze how, through the composition of the characters and through the eyes of the witness-narrator, the questions about the construction of an African-American identity are presented and discussed, and how it is possible to perceive in the novel The Eye Bluest, (1970), the resumption about the discussion about the concept of blackness. One of the interests in this analysis is to investigate the way oppression is imposed on a black community, established in the north of the US. Both blackness and Afro-American identity are represented in Morrison´s fiction through the voice of the witness-narrator that builds a critical point of view on the white north american society and on the black community, which in many ways, reduplicates the prejudiced look launched on itself and on its members. The criticism is also established through the representation of the main character, Pecola. The research is based on analysis of the novel of the American writer Toni Morrison. The Bluest Eye is the first novel published by the author and constitutes itself as a report of the witness-narrator ´s experiences, and as the social and cultural representation of a certain community in a very precise socio-historical moment. To perform the analysis, it was necessary to establish the concepts of cultural identity, blackness, subjectivity and (Afro) American history, taking into account the fictional discourse.